(untitled) (International Journal of Food and Nutritional Sciences, 2022)
At the Agricultureal Research Farm of Rama University, Mandhana, Kanpur (U.P.), the current study, " Effect of Azotobacter, Azospirillum, PSB on Chemical Parameters and its Combinations with Chemical Fertilizers of Okra [Abelmoschus esculentus (L.) Moench] cv. Parbhani Kranti," was conducted in summer season . Ascorbic acid, acidity, and moisture percentage were all optimized, according to the data. when we apply fertilizers at the 40% RDF for NPK, 75% PSB, 55% Azotobacter, and 60% Azospirillum recommended dosages.